Cost Analysis for a Supplier in an Inflationary Environment with Stock Dependent Demand Rate for Perishable Items. (17th December 2014) - Jain, Madhu; Sharma, G. C.; Rani, Varsha
Abstract : The present study is concerned with the cost modeling of an inventory system with perishable multi-items having stock dependent demand rates under an inflationary environment of the market. The concept of permissible delay is taken into account. The study provides the cost analysis of inventory system under the decision criteria of time value of money, inflation, deterioration, and stock dependent demand. Numerical illustrations are derived from the quantitative model to validate the results. The cost of inventory and optimal time are also computed by varying different system parameters. The comparison of these results is facilitated by computing the results with neurofuzzy results.